Inflammatory Animal Model for Parkinson's Disease: The Intranigral Injection of LPS Induced the Inflammatory Process along with the Selective Degeneration of Nigrostriatal Dopaminergic Neurons. (17th April 2011) - Machado, A.; Herrera, A. J.; Venero, J. L.; Santiago, M.; de Pablos, R. M.; Villarán, R. F.; Espinosa-Oliva, A. M.; Argüelles, S.; Sarmiento, M.; Delgado-Cortés, M. J.; Mauriño, R.; Cano, J.
Abstract : We have developed an animal model of degeneration of the nigrostriatal dopaminergic neurons, the neuronal system involved in Parkinson's disease (PD). The implication of neuroinflammation on this disease was originally established in 1988, when the presence of activated microglia in the substantia nigra (SN) of parkinsonians was reported by McGeer et al. Neuroinflammation could be involved in the progression of the disease or even has more direct implications. We injected 2 μg of the potent proinflammatory compound lipopolysaccharide (LPS) in different areas of the CNS, finding that SN displayed the highest inflammatory response and that dopaminergic (body) neurons showed a special and specific sensitivity to this process with the induction of selective dopaminergic degeneration. Neurodegeneration is induced by inflammation since it is prevented by anti-inflammatory compounds. The special sensitivity of dopaminergic neurons seems to be related to the endogenous dopaminergic content, since it is overcome by dopamine depletion. Compounds that activate microglia or induce inflammation have similar effects to LPS. This model suggest that inflammation is an important component of the degeneration of the nigrostriatal dopaminergic system, probably also in PD. Anti-inflammatory treatments could be useful to prevent or slow down the rate of dopaminergic degeneration in this disease.